Mangrove area development strategy wonorejo as ecotourism in surabaya - Murtini, S; Kuspriyanto; Kurniawati, A (Journal of physics. Conference series, 2018)
Wonorejo mangrove ecotourism is a natural attraction that is increasingly in demand by the community. From year to year, this mangrove ecotourism shows an increase in the number of visitors so it is necessary to know the carrying capacity and development strategy to keep visitors comfortable in the location of tourism. The purpose of this research is to determine development strategies undertaken by the government. The research approach is descriptive quantitative by using survey method. The subject of research is the management of ecotourism area while the object of research includes mangrove, biota object and wide of an area. Sources of data obtained from interviews with parties related to the management of mangrove eco-tourism Wonorejo. Development strategy by using SWOT analysis. The results showed that the collation of the I-EFAS value indicates the position of P (2,35: 2,61) in quadrant I or growth, it's the right strategy for the development of Wonorejo mangrove eco-tourism area is an aggressive strategy.